SIMILARITIES AND DIFFERENCES IN THE APPLICATION OF SHOCK-TAINMENT TECHNOLOGY IN UZBEKISTAN AND FRANCE MEDIA MATERIALS - Boboyev, Ulash (Журнал иностранных языков и лингвистики, 2023)
The article is devoted to the current and little-studied issues of comparative analysis of the use of the shock-taming literary tool in the media of Uzbekistan and France. The purpose of the article is to identify the similarities and differences in the use of shock-teaching technology in media materials of Uzbekistan and France. Research methods: analysis of scientific literature and information materials of Uzbek and French mass media, comparative analysis, induction, deduction, generalization and complex analysis. The author of the article concludes that similarities in the use of shock technology in media materials of Uzbekistan and France are reflected in its compositional nature (the same shock means, but in different proportions). The differences are related to the language and cultural characteristics of the two countries. In France, negative, direct and rough hitting prevails, in Uzbekistan it is used more selectively, it mainly has a positive color and represents the successes and achievements of the people and the state. emphasizes (there are also negative meanings, but less often) and more mildly, they mostly cause surprise and reader’s regret).